Strategies for Reuse and Sharing among Data Scientists in Software Teams - Epperson, Will; Wang, April; DeLIne, Robert; Drucker, Steven (ICSE 2022, 2022)
Effective sharing and reuse practices have long been hallmarks of proficient software engineering. Yet the exploratory nature of data science presents new challenges and opportunities to support sharing and reuse of analysis code. To better understand current practices, we conducted interviews (N=17) and a survey (N=132) with data scientists at Microsoft, and extract five commonly used strategies for sharing and reuse of past work: personal analysis reuse, personal utility libraries, team shared analysis code, team shared template notebooks, and team shared libraries. We also identify factors that encourage or discourage data scientists from sharing and reusing. Our participants described obstacles to reuse and sharing including mismatched incentives to create shared code, difficulties in making data science code modular, and a lack of tool interopoerability. We discuss how future tools might help meet these needs.